2019
DOI: 10.1111/dmcn.14330
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral phenotype and sleep problems in SATB2‐associated syndrome

Abstract: Aim To determine the nature and frequency of behavioral phenotypes and sleep disturbances in individuals with SATB2‐associated syndrome (SAS). Method The Strengths and Difficulties Questionnaire (SDQ) and an age‐appropriate sleep questionnaire were distributed to the parents of individuals with SAS. All scores were compared to available normative data. Results Thirty‐one individuals completed the assessment (18 females, 13 males; mean age 7y 4mo [SD 4y 1mo], range 2–16y). Individuals with SAS had significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…A broad spectrum of behavioral issues has been reported, including pleasant personality, irritability, hyperactivity, sleep problems, sensory issues, stereotyped repetitive movements, and Rett syndrome-like phenotypes[ 3 , 7 , 22 , 27 , 28 ]. Nonspecific brain abnormalities detected by MRI are found in half of affected individuals, including ventricle enlargements, thin corpus callosum, enlarged perivascular spaces, and abnormal myelinization in white matter[ 7 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A broad spectrum of behavioral issues has been reported, including pleasant personality, irritability, hyperactivity, sleep problems, sensory issues, stereotyped repetitive movements, and Rett syndrome-like phenotypes[ 3 , 7 , 22 , 27 , 28 ]. Nonspecific brain abnormalities detected by MRI are found in half of affected individuals, including ventricle enlargements, thin corpus callosum, enlarged perivascular spaces, and abnormal myelinization in white matter[ 7 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…SATB2-associated syndrome (SAS; glass syndrome, OMIM 612313) is a multisystemic autosomal dominant disorder with a well-established neurodevelopmental phenotype characterized by severe speech delay, autistic tendencies, and behavioral abnormalities. [1][2][3] From the craniofacial perspective, individuals with SAS are known to have a high frequency of palatal and dental anomalies often related to morphological changes affecting the jaw and lower face including micrognathia, facial asymmetry, a triangular appearance of the lower face, and a prominent chin. 4,5 Since Satb2 was identified as a gene associated with cleft palate in humans, 6 experiments in mice and other vertebrates have shown that Satb2 is expressed early in development in the first pharyngeal arch (PA1), the tissue that later gives rise to the jaw.…”
Section: Introductionmentioning
confidence: 99%
“…SATB2‐associated syndrome (SAS; glass syndrome, OMIM 612313) is a multisystemic autosomal dominant disorder with a well‐established neurodevelopmental phenotype characterized by severe speech delay, autistic tendencies, and behavioral abnormalities 1–3 . From the craniofacial perspective, individuals with SAS are known to have a high frequency of palatal and dental anomalies often related to morphological changes affecting the jaw and lower face including micrognathia, facial asymmetry, a triangular appearance of the lower face, and a prominent chin 4,5 …”
Section: Introductionmentioning
confidence: 99%
“…Likewise, composite nonverbal cognitive scores can display variability from mild to severe [3,7]. The broad range in severity can also be found for many of the other systemic features, including seizures (some individuals have severe epileptic encephalopathy), behavioral problems (antipsychotic medications or management at inpatient facilities for mental health issues have been reported), sleeping difficulties (including the need for high doses of multiple medications to aid with sleep), skeletal complications (some individuals have had recurrent fractures requiring treatment with medications for metabolic bone issues), dental anomalies (significant primary and secondary dentition problems have been reported), and growth delay (some individuals have needed aggressive feeding interventions) [8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%